Crowdfunding as a tool to support sustainability‐oriented initiatives: Preliminary insights into the role of product/service attributes. (4th September 2019) - Testa, Stefania; Roma, Paolo; Vasi, Maria; Cincotti, Silvano
Abstract: A common goal of current research seems to uncover whether crowdfunding (CF) could be considered an effective way to support sustainability‐oriented initiatives in securing funding, due to diverging results emerging from literature. We claim that the objective of proving whether CF may benefit sustainability‐oriented initiatives could be misplaced; rather, we deem more fruitful to understand how critical are some attributes of products/services pursued within CF campaigns to benefiting sustainability‐oriented initiatives and increasing their odds of success in CF. We focus on food‐related projects as in this sector, sustainability issues apply more than to any other human activities and construct a unique sample of food CF campaigns launched and ended in the European Economic Area countries on the world's most popular reward‐based CF platform, that is, Kickstarter. We identify campaigns with a sustainability orientation and perform an in‐depth qualitative analysis, which allows us to classify them into meaningful clusters and subclusters. Our research suggests that the emphasis on egoistic/self‐centered product attributes, rather than on altruistic/society‐centered attributes, is generally more crucial to facilitate CF support to sustainability‐oriented projects. However, the emphasis on altruistic/society‐centered attributes emerges to be more beneficial for initiatives specifically supporting local products. Our results also suggest that reward‐based CF is not suitable for sustainability‐oriented projects targeting disadvantaged individuals/groups. These results offer both theoretical and empirical contributions to the literature as well as practical implications.